Validation of collection and anaerobic fermentation techniques for measuring prebiotic impact on gut microbiota - Alexander W. Thorman; Ardythe L. Morrow; Andre Groeneveld; Arjen Nauta; David S. Newburg (Elsevier, 2024)
Background: Defining the ability of prebiotic dietary carbohydrates to influence the composition and metabolism of the gut microbiota is central to defining their health impact in diverse individuals. Many clinical trials are using indirect methods. This study aimed to validate collection and fermentation methods enabling their use in the context of clinical studies. Methods and Results: Parameters tested included stool sample acquisition, storage, and growth conditions. Stool from 3 infants and 3 adults was collected and stored under varying conditions. Samples were cultured anaerobically for two days in the presence of prebiotics, whereupon optical density and pH were measured across time. Whole genome shotgun sequencing and NMR metabolomics were performed. Neither the type of collection vial (standard vial and two different BD anaerobic collection vials) nor cryopreservation (-80 °C or 4 °C) significantly influenced either microbial composition at 16 h of anaerobic culture or the principal components of the metabolome at 8 or 16 h. Metagenomic differences were driven primarily by subject, while metabolomic differences were driven by fermentation sugar (2'-fucosyllactose or dextrose). Conclusions: These data identified a feasible and valid approach for prebiotic fermentation analysis of individual samples in large clinical studies: collection of stool microbiota using standard vials; cryopreservation prior to testing; and collecting fermentation read-out at 8 and 16 hr. Thus, fermentation analysis can be a valid technique for testing the effects of prebiotics on human fecal microbiota.